Tax Policy, Strategy Decision Making, Economic Environment on Finance Performance with Organizational Culture as a Moderator - Endro Andayani (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Indonesia’s dynamic manufacturing sector is heavily influenced by tax regulations, strategic decisions, and macroeconomic conditions. However, the impact of these factors on company financial performance remains underexplored, particularly in relation to organizational culture as a moderating variable. This study aims to examine the effect of tax policy, strategic decision making, and economic environment on financial performance, with organizational culture as a moderator. The research involved 350 managerial-level respondents from both listed and unlisted manufacturing companies on the Indonesia Stock Exchange (IDX). Data were collected via online questionnaires disseminated through social media platforms and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS. The results reveal that tax policy positively affects financial performance, while economic environment has a negative effect. Strategic decision making, however, does not significantly influence financial performance. Furthermore, organizational culture does not significantly moderate the relationship between tax policy, strategic decision making, or economic environment and financial performance. These findings offer insights for tax authorities and policymakers to refine tax policies, particularly in the context of the harmonization of tax regulations law and business-related incentives. The novelty of this study lies in the inclusion of a new indicator tax rate in the tax policy construct.